Orientational anisotropy due to molecular field splitting in sulfur 2p photoemission from CS2 and SF6 - theoretical treatment and application to photoelectron recoil - Kukk, Edwin; Niskanen, Johannes; Travnikova, Oksana; Berholts, Marta; Kooser, Kuno; Peng, Dawei; Ismail, Iyas; Piancastelli, Maria Novella; Püttner, Ralph; Hergerhahn, Uwe; Simon, Marc (Royal Society of Chemistry, 2025)
Photoelectron recoil strongly modifies the high kinetic energy photoemission spectra from atoms and molecules as well as from surface structures. In most cases studied so far, photoemission from atomic-like inner-shell or core orbitals has been assumed to be isotropic in the molecular frame of reference. However, in the presence of molecular field splitting of p or d orbitals, this assumption is not justified per se. We present a general theoretical treatment, linking the orientational distribution of gas-phase molecules to the electron emission and detection in a certain direction in the laboratory frame. The approach is then applied to the S 2p photoemission from a linear molecule such as CS2 and we investigate, how the predicted orientational anisotropies due to molecular field splitting affect the photoelectron recoil excitations. Lastly, experimental S 2p high-kinetic-energy photoelectron spectra of SF6 and CS2 are analyzed using the modeled recoil lineshapes representing the anisotropy-affected recoil effects.